Pembelajaran Berbasis Kearifan Lokal Di Sekolah Dasar: Sebuah Kerangka Konseptual - Naela Khusna Faela Shufa (INOPENDAS: Jurnal Ilmiah Kependidikan, 2018)
Education is one of important element in a life. Because through education someone can develop knowledge, insight, values and character even as an effort of cultural inheritance. Therefore it is necessary cooperation from all lines of education as an effort to achieve learning objectives that not only supply knowledge, but also the character and love of diversity. One of them is by integrating local wisdom in learning. But in reality many teachers who have not integrated local wisdom in learning so that the goal of education has not been achieved other than that not yet know the local wisdom in the environment. Based on these problems, conducted a conceptual study about learning based on local wisdom. This conceptual study will discusse about how  the importance of integrating local wisdom in learning as an effort to create learning that not only supply students of knowledge but also instills a sense of love for local diversity in their environment, the impact from implementation learning based on local wisdom. And how the teacher steps in integrating the local wisdom. Through this study is expected useful for the teachers to participate in designing and implementing learning based on local wisdom in primary schools.